Analisis Kekuatan Lentur Komposit Berbasis Serat Daun Alam sebagai Alternatif Material Bilah Turbin - Novia Arista Dwi Ramadina; Yuliyanto Yuliyanto; Muhammad Subhan (Jurnal Inovasi Teknologi Terapan, 2026)
Wind energy is one of the most promising renewable energy sources to support the transition toward sustainable energy systems, making the selection of strong and environmentally friendly wind turbine blade materials essential. This study aims to assess the potential of natural fibers as composite reinforcement, with a particular focus on flexural performance. Three types of natural fibers were compared: ijuk fiber (Arenga pinnata), pineapple leaf fiber, and corn husk fiber. Composite specimens were produced using polyester resin as the matrix with a 5% fiber volume fraction (95:5 ratio), and all fibers were pretreated through two hours of alkaline immersion. Test samples were fabricated following ASTM D790 standards with dimensions of 150 × 12.5 × 3 mm and evaluated using a Zwick Roell Z020 universal testing machine at the Materials Laboratory of Politeknik Manufaktur Negeri Bangka Belitung. The results revealed that ijuk fiber–reinforced composites achieved the highest average flexural strength of 57.3 MPa, followed by PALF at 47.5 MPa, while corn husk fiber produced the lowest value at 29.33 MPa. One-way ANOVA confirmed significant differences among the three fiber groups (p < 0.05). Overall, ijuk fiber demonstrated the greatest potential as a sustainable and high-performing reinforcement material for composite applications.